Newly described species of Endiandra (Lauraceae) from New Guinea - Deby Arifiani (BRIN Publishing (Penerbit BRIN), 2012)
Two new species of Endiandra (Lauraceae), i.e. Endiandra areolata Arifiani and Endiandra lanata Arifiani are described from New Guinea. Both species have staminal glands, but their form is different in the two species.Â Moreover, E. areolata Arifiani is characterized by its prominent areolation formed by the minor venation, and E. lanata Arifiani is easily recognized by the presence of a dense curly indument on its twig, leaves, inflorescences and flowers.